'Practices of self': Embodied memory work, performance art, and intersectional activism in Namibia. (June 2023) - Brandt, Nicola
Cultural commemoration in the form of embodied memory was practiced in Namibia long before German colonial occupation in the 1880s and the War of Independence against South Africa from 1966 to 1989. In recent years, Namibian artists have been offering alternative forms of embodied memory transmission related to these histories. I argue that much of this work is inextricably linked to a new wave of decolonial activism in the country. These practices highlight questions related to history and memory and are a counterpoint to state-sanctioned memorialization. Some of the recurrent themes are efforts to work through traumatic legacies connected to German colonialism and apartheid, but also to intersectional violence tied to contemporary patriarchy and identity politics. In these settings, queer and feminist methodologies provide a departure point for this embodied memory work in an attempt to go beyond colonial and tribal legacies and nationalized identity politics.